2020
DOI: 10.3390/land9050161
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Orientation Skill for Landscape Architecture Education and Professional Practice

Abstract: Professional landscape architecture organizations have requested training from educational institutions based on new skills and methodologies in the curriculum development of students. Landscape architects need to visualize and evaluate the spatial relationships between the different components of the landscape using two-dimensional (2D) or three-dimensional (3D) maps and geospatial information, for which spatial orientation skills are necessary. The data from six workshops conducted throughout the 2010–2020 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In this research, we tried to find a difference in the spatial orientation with respect to the others, since in the proposed training tasks took into account working with architectural spaces at real scales, which demanded navigation capabilities and orientation in walkarounds much more related to that spatial orientation component. However, this difference has not yet been found, which suggests that it should be followed this tendence of specific analysis of spatial orientation in trainings related to geographic and cartographic tasks [30,31,61,62].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this research, we tried to find a difference in the spatial orientation with respect to the others, since in the proposed training tasks took into account working with architectural spaces at real scales, which demanded navigation capabilities and orientation in walkarounds much more related to that spatial orientation component. However, this difference has not yet been found, which suggests that it should be followed this tendence of specific analysis of spatial orientation in trainings related to geographic and cartographic tasks [30,31,61,62].…”
Section: Discussionmentioning
confidence: 91%
“…In this research, we tried to find a difference in the spatial orientation with respect to the others, since in the proposed training tasks took into account working with architectural spaces at real scales, which demanded navigation capabilities and orientation in walkarounds much more related to that spatial orientation component. However, this difference has not yet been found, which suggests that it should be followed this tendence of specific analysis of spatial orientation in trainings related to geographic and cartographic tasks [30,31,61,62] We consider that this study serves as a clarifying contribution so that the analyses of spatial skills improvement can follow the proposal of Carroll [13] and backed by numerous authors [27,28,63] who propose two components for spatial skills: spatial relations, which contain the spatial orientation, and spatial visualization.…”
Section: Discussionmentioning
confidence: 93%
“…Case studies are necessary for landscape architecture students. In landscape architecture classes, teachers are usually required to present students with various works or cases through pictures or videos to transfer knowledge and skills [18]. However, as time goes by, students increasingly resist this traditional way of appreciation.…”
Section: Landscape Architecture Educationmentioning
confidence: 99%
“…By analyzing the studies of VR technology and landscape education, we found that most of the studies adopted 3D model-based VR technology. For instance, Carbonell et al [18] conducted an experiment with the 3D model-based heavy VR equipment but did not receive good experimental results, which might have been caused by the equipment. Chang, Chou, Chuang, Li, and Tsai [40] also developed a new VR technology and carried out an experiment.…”
Section: Landscape Architecture Educationmentioning
confidence: 99%
See 1 more Smart Citation